Microstructuring of Thermo-Mechanically Highly Stressed Surfaces : Final Report of the DFG Research Group 576 - Denkena, Berend; Rienäcker, Adrian; Knoll, Gunter; Bach, Friedrich-Wilhelm; Maier, Hans Jürgen; Reithmeier, Eduard; Dinkelacker, Friedrich (Lecture Notes in Production Engineering, 2015)
This contributed volume presents the final research results of the DFG Research Group 576, which is a joint initiative of five different institutes of the Leibniz Universität Hannover and the Universität Kassel, Germany. The research of the DFG Research Group 576 focuses on improving the tribological behavior of thermomechanically highly stressed surfaces, particularly on cylinder liner for combustion engines. The target audience primarily comprises researchers and experts in the field but the book may also be beneficial for graduate students who want to specialize in the field.